Exploring drivers and prevention strategies for sexual violence among adolescent girls and young women in Kicukiro, Rwanda - Kawonga, Wongani Patricia; Livingstone, Sam M.; Ndaimani, Augustine; Sibomana, Jean Pierre; Waka, Tsion Yohannes; Mhlanga, Maxwell; Mclellan, Andrew (Frontiers in Reproductive Health, 2025)
IntroductionSexual violence against adolescent girls and young women (AGYW) is a pervasive issue globally, with particularly high prevalence in sub-Saharan Africa. This study explores the drivers and prevention strategies for sexual violence among AGYW in Kicukiro, Rwanda.MethodsA descriptive exploratory design guided by the socioecological model and feminist standpoint theory was employed. In-depth interviews were conducted with 13 AGYW participating in a mentorship program and 5 male community members. Data was analyzed using thematic analysis to identify key drivers and potential prevention strategies.ResultsFour themes emerged: (1) empowering mentorship programs, (2) tiered drivers of sexual violence, (3) optimizing violence-mitigating resources, and (4) interference with judicial processes. Key drivers of sexual violence included substance use, transactional sexual relationships, inadequate family protection, entrenched gender stereotypes, and limited legal literacy.ConclusionFindings underscore the need for multifaceted interventions that address systemic and cultural barriers, strengthen legal frameworks, and expand community-based programs. Addressing sexual violence requires a holistic approach, integrating empowerment initiatives, robust community engagement, and legal reforms to create safer environments for AGYW. The mentorship program's success suggests scalability across other settings.